Is the Andromeda Galaxy Approaching our Galaxy Milky Way? - Harutyunian, H. A.; Grigoryan, A. M.; Khasawneh, A.; Torosyan, A. A.
No doubt that the dark energy carrier interacts with the baryonic matter. Due to this interaction some portions of energy are transferring gradually to all baryonic objects and their systems without any exception at all hierarchical levels of the baryonic world. The consequences of the energy transfer are quite dramatic for all objects. The most dramatic changes take place at the nuclear level. Objects of this particular level have the universal property of converting energy into mass, which ultimately affects the cosmic objects of all levels and the baryonic Universe as whole. Hear we consider the side effect of growing mass of nuclei. That is the inevitable blueshift of spectral lines of atoms possessing higher mass nuclei compared with the atoms having nuclei of lesser mass. We hypothesize here that the Andromeda galaxy spectral blueshift can be resulted by Doppler effect as accepted but due to the more advanced evolution compared with our galaxy but not by its approaching velocity.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture